Historical overview, advancements, and future prospects of coalfield structure research in China - Daiyong CAO; Yiwen JU; Yucheng XIA; Bo JIANG; Shuzheng NING; Yingchun WEI; Anmin WANG; Xiaoming LI; Wenfeng ZHAN; Huantong LI; Lu WANG; Zhuocheng CAI (Meitian dizhi yu kantan)
BackgroundCoalfield structures represent a basic aspect of coalfield geology. In China, research into this domain has a history of over a century, yielding numerous results after undergoing exploration, learning, and innovation. These results have played a positive role in the long-term, stable coal supply in China. Amidst the ongoing energy structure optimization and the transformation and upgrading of coalfield geology in China, it is both practically and historically significant to review the history of coalfield structure research, summarize relevant experience, and contemplate future directions of the research under emerging circumstances.Methods Based on literature analysis, as well as the long-term research practices of the authors’ team, this study discusses the disciplinary attribute of coalfield structure research, reviews the history of this field both at home and abroad, and summarizes major achievements in China. Furthermore, it analyzes the issues and challenges of coalfield structure research in China and articulates future trends. By integrating advanced international geological theories with domestic coalfield geological practices, China’s coalfield geologists have established theoretical and methodological systems with distinctive Chinese characteristics for coalfield structure research. Advances and ProspectsBy integrating advanced international geological theories with domestic coalfield geological practices, China’s coalfield geologists have established theoretical and methodological systems with distinctive Chinese characteristics for coalfield structure research. Recent important achievements made in the coalfield structure research in China include: (1) a deep understanding of the characteristics and spatiotemporal differences of coalfield structures across the country, (2) continuous, in-depth research on regional structures in coalfields and coal basin structures, (3) the development of the concept of structure-controlled coals, (4) significant breakthroughs in research on coalfield detachment structures, (5) significant achievements in research on coal deformation and metamorphism, (6) attention being paid to the controlling effects of structures on coal-measure minerals, and (7) the emergence of mine structure research as a popular direction. The complexity of coalfield geological structures in China determines the important role of coalfield structure research in the exploration and exploitation of coal resources. In the next few years, it is necessary to deepen and broaden the fields of coalfield structure research in China by keeping pace with the advancements in contemporary geological science and technology, as well as national and industrial demands. Moreover, it is recommended that the theoretical and methodological systems of coalfield structures in China should be further improved by persisting in innovations while preserving distinctive Chinese characteristics.